RESPON BEBERAPA SIFAT FISIKA TANAH ALUVIAL PADA KOMBINASI KOMPOS SAMPAH KOTA DAN PUPUK KANDANG SAPI SETELAH DITANAMI PAKCOY - Wiwik Ambarsari; Yulina, Henly (Program Studi Agroteknologi Faperta UNIBBA, 2022)
Alluvial soil in this study is a vertic endoaquepts paddy soil type, which is an alluvial paddy soil with a wide distribution in the Pantura area, West Java, originating from a long river deposition system with various types of erosion materials. This soil has a high mineral content of easily weathered sand, especially feldspars. The presence of quartz, orthoclase and sanidine minerals indicates the presence of acidic materials. This also causes the content of chemical elements in this alluvial deposit to be low, so it is necessary to add organic materials such as municipal waste compost and cow manure which can improve the physical, chemical and biological properties of the soil. The aim of the study was to determine the response of several physical properties of alluvial soil to a combination of municipal waste compost and cow manure after being planted with pakcoy in Alluvial, Indramayu. The objective of this research was to find out relationship between water content and soil bulk density to the harvest of pakcoy after combined with municipal waste compost and cow manure in Alluvial, Indramayu. This study used a randomized block design factorial with two factors. The first factor is municipal waste compost and the second factor is cow manure. Each of them consisted of 4 levels : 0%, 3.0%, 6.0%, and 9.0% with two replication. The results showed that there was no interaction between municipal waste compost with cow manure and municipal waste compost with cow manure had no significant effect on soil water content of pakcoy plants after harvest. Meanwhile, cow manure has an independent effect on soil bulk density in pakcoy plants after harvest. The largest decrease in soil density occurred at a dose of 9.0% (k4), but the addition of cow manure at a dose of 3.0% (k2) was able to reduce the soil bulk density. This K2 treatment was not significantly different from the other treatments. A decrease in soil density to 1.15 g cm-3 (k2) is considered ideal for mineral soils, because in general the bulk density of mineral soils is between 1.1 – 1.6 g cm-3.